THE IMPACT OF TRAVEL RISK PERCEPTION IN COVID 19 AND TRAVEL ANXIETY TOWARD TRAVEL INTENTION ON DOMESTIC TOURIST IN INDONESIA - Angguni, Frisye; Lenggogeni, Sari (2021)
This research aims to find out the relationship between travel risk perceptions in Covid 19 and travel anxiety, toward travel intention among domestic tourists in Indonesia during the Covid 19 Pandemic. The population in this study are all potential domestic tourists in Indonesia with sampling techniques use in probability sampling. This research Data were collected from 225 potential domestic tourists via an online survey and analyzed using Partial Least Square (PLS) with structural equation modeling (SEM). The results of this study revealed that health crises that occur such as the Covid 19 Pandemic can lead to negative travel risk perceptions of the tourists, such as travel bans issues, travel restrictions, and susceptibility to getting infected by Covid 19 while traveling. Furthermore, the travel risk perception then affects the travel anxiety and travel intention of these tourists. In addition to seeing tourists' perceptions of risk, travel anxiety, and their effect on travel intentions, the results of this study are also complemented by suggestions and implications for stakeholders in the tourism industry in Indonesia who are expected to be treated to face these posts. -Covid 19 pandemic situations. Psychological factors such as anxiety are found mediated between tourists' perceptions of travel risks during the Covid 19 period and their intention to travel.